2021
DOI: 10.3390/app11125387
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Reliability Assessment for Small Sample of Failure Data of Dumper Diesel Engines Based on Power Law Process and Maximum Likelihood Estimation

Abstract: Dumpers or dump trucks are used all over the world to move overburden from many opencast mines. Diesel engines are the main driving force behind the trucks. The frequency of damage due to the failure of diesel engines is enormous. Therefore, efforts are necessary to analyze failure to reduce the downtime periods. A detailed analysis of engine failure at the subsystem level needs to be done. Reliability analysis and maintenance planning remain the norm in this regard. The obstacle faced while analysing the reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…As presented in [1], to this day, research articles highlighting analytical methods on small data sets are practically limited. From the literature review presented [1], it is revealed that most of the studies conducted thus far using scarce failure data are less.…”
Section: Reliability and Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in [1], to this day, research articles highlighting analytical methods on small data sets are practically limited. From the literature review presented [1], it is revealed that most of the studies conducted thus far using scarce failure data are less.…”
Section: Reliability and Risk Assessmentmentioning
confidence: 99%
“…As presented in [1], to this day, research articles highlighting analytical methods on small data sets are practically limited. From the literature review presented [1], it is revealed that most of the studies conducted thus far using scarce failure data are less. The methods used for reliability analyses for small number data are mostly the Bayesian approach, FMECA and Monte Carlo method.…”
Section: Reliability and Risk Assessmentmentioning
confidence: 99%
“…It can be observed from Table 3 that the level of heterogeneity value is negative for self-starting, fuel supply, lubrication, and cooling subsystems [27][28][29][30]. Negative values for the level of heterogeneity can be treated as equal to zero [10].…”
Section: Meta-analysis Testmentioning
confidence: 99%
“…A reliability analysis of engine subsystems is essential in the formulation of maintenance strategies, which will decrease the downtime of an engine and increase its availability. A main obstacle was the deficiency of adequate data for the appropriate statistical analyses [23][24][25][26][27][28][29][30]. The present study gives specific guidelines for using the metaanalysis test, which will solve the problem related to small-size failure data.…”
Section: Introductionmentioning
confidence: 99%
“…The damage threshold distribution of the main coupling port of the system is obtained by system-level effect threshold tests and statistical distribution fitting methods. However, for practical assessment application, the number of system-under-test (SUT) samples is often limited to less than the sample number required for ordinary statistical distribution fittings [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%